Remnant cholesterol, coronary atheroma progression and clinical events in statin-treated patients with coronary artery disease. (July 2020) - Elshazly, Mohamed B; Mani, Preethi; Nissen, Steven; Brennan, Danielle M; Clark, Donald; Martin, Seth; Jones, Steven R; Quispe, Renato; Donnellan, Eoin; Nicholls, Stephen J; Puri, Rishi
Aim: Remnant cholesterol has been proposed to promote atherosclerotic cardiovascular disease independent of low-density lipoprotein cholesterol, yet the underlying mechanisms are not well understood. We aimed to study the association of remnant cholesterol with coronary atheroma progression and clinical events. Methods: We analyzed data from 5754 patients with coronary artery disease undergoing serial intravascular ultrasonography who were enrolled in 10 trials examining various medical therapies. Remnant cholesterol was calculated as (non-high-density lipoprotein cholesterol – low-density lipoprotein cholesterol (estimated using the Hopkins–Martin equation)). Changes in percentage atheroma volume and 2-year major adverse cardiovascular events were compared across various levels of remnant cholesterol, and multivariable models were used to assess the independent relationship of remnant cholesterol with changes in percentage atheroma volume. Results: The mean age was 58.1 ± 9.2 years, 28% were women and 96% received a statin. Percentage atheroma volume progression (changes in percentage atheroma volume > 0) occurred in a linear fashion at on-treatment remnant cholesterol levels of 25 mg/dL or greater. The highest on-treatment remnant cholesterol quartile demonstrated greater percentage atheroma volume progression (+0.53 ± 0.26 vs. –0.15 ± 0.25%, P  < 0.001) and 2-year major adverse cardiovascular events (23% vs. 14%, log–rank P  < 0.001) compared with the lowest. In multivariable analyses, changes in percentage atheroma volume significantly correlated with on-treatment remnant cholesterol ( P  < 0.001] independent of low-density lipoprotein cholesterol, apolipoprotein B, C-reactive protein, high-density lipoprotein cholesterol levels and clinical risk factors. Changes in percentage atheroma volume also significantly correlated with changes in remnant cholesterol following multivariable adjustment. Conclusions: In statin-treated patients with atherosclerotic cardiovascular disease, remnant cholesterol was associated with coronary atheroma progression regardless of conventional lipid parameters, C-reactive protein or clinical risk factors. Higher remnant cholesterol levels also correlated with higher major adverse cardiovascular events. These data support further investigations into remnant cholesterol-lowering interventions in statin-treated patients harboring residual atherosclerotic cardiovascular disease risk.